Anthelmintic resistance of gastrointestinal nematodes in cattle in Brazil and Argentina-current status and global perspectives - Borges, Fernando de Almeida; Do Amarante, Alessandro Francisco Talamini [UNESP]; Lopes, Welber Daniel Zaneti; Canton, Candela; Alvarez, Luis; Lifschitz, Adrian (FapUNIFESP (SciELO), 2024)
This review outlines the current state of anthelmintic resistance (AHR) of gastrointestinal nematodes (GINs) among cattle in Argentina and Brazil, emphasizing the economic repercussions, animal health and welfare. The analysis explores factors associated with AHR and proposes a potential solution: the use of drug combinations. Both countries are grappling with a severe AHR scenario in cattle, having progressed through incipient, established, and advanced phases, leading to extreme cases of animal mortality due to ineffective control strategies. Genera such as Cooperia and Haemonchus have the highest reports of resistance, with Oesophagostomum radiatum also posing significant problems. While oral benzimidazoles and levamisole remain effective in most herds, moxidectin is entering an advanced resistance phase, and avermectins are increasingly deemed ineffective. The review explores the impact ofclimate, mixed grazing, animal movement and other husbandry practices, and the relationship between ectoparasite control and the emergence of resistant helminths. Notably, the discussion includes the strategic use of drug combinations as a valuable approach to address resistant GINs control in livestock, highlighting its significant potential to mitigate the challenges posed by AHR in the cattle industry of these countries.
Resistência anti-helmíntica em nematódeos gastrintestinais de bovinos no Brasil e Argentina-situação atual e perspectivas globais
Keywords: cattle health; Cooperia; drug combinations; Haemonchus; livestock management